Teenagers Psychology In Young Wrestlers (Zien Journal of Social Sciences and Humanities, 2022)
The article is about young wrestlers and the tasks and research methods of pedagogical psychology, biological and social factors in personality formation, the relationship between mental development and education. It is intended for university students, as well as educators working with children and students of different ages.